Tutorials in population neuroimaging: Using epidemiology in neuroimaging research - Godina, Sara; Jacob, Mini E.; Ganguli, Mary (Frontiers in Neuroimaging, 2022)
Epidemiology is the foundation of all public health research and practice. Epidemiology confers many important uses for the advancement of neuroimaging research. Epidemiology serves as a framework to organize pieces of data and guide critical thinking in the research process from the early stages of study design to the end goal of reaching appropriate inferences. Epidemiology accounts for the profound heterogeneity in populations, thoroughly describes study samples, and identifies consequential threats to study validity. Finally, epidemiology is a discovery tool that can lead researchers to uncover new risk factors, disease states, and subpopulations. The neuroimaging investigator with a grasp of the principles of epidemiology is in a unique position to undertake valid clinical epidemiology and etiological research.